Rachunkowość zarządcza w przedsiębiorstwach internetowych - Wierzbiński, Marcin (Management Accounting in E-Business Companies, 2005)
In the first section of the article author presents the circumstances of growth and then the downfall of e-business companies at the end of twenty century. In this section there are also characterized main success factors of running business in Internet. The two sections are grounds for determining hints that facilitate developing the system supporting management of e-business companies based on management accounting instruments. In the article author shows how the system changes and which management accounting instruments are used in the different stages of e-business development.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 372-381